Design and construction of telegram bot-based data breach preprocessing application for cyber threat intelligence in institution x - Gandhara, Seto; Satria, Tegar Pandu; Saragih, Hondor (Jurnal Mandiri IT, 2025)
Data breaches pose a significant threat in today's digital landscape, especially for organizations handling sensitive information, such as government institutions. These incidents can result in serious consequences, including risks to national security, loss of public trust, and financial harm. Institution X, an Indonesian organization dedicated to cyber threat prevention, faces challenges due to the high volume of unstructured and "dirty" leaked data, often shared via hidden platforms like the dark web and Telegram. To address this issue, a Telegram bot-based application was designed and developed using the Rapid Application Development (RAD) method. The application automates data collection, cleaning, and preprocessing, with features such as keyword-based search and CSV file conversion. It was built using Python and deployed through the Replit cloud platform, utilizing the Telebot library to interact with Telegram APIs. Internal testing covered six usage scenarios, including keyword processing, multi-file handling, and unauthorized access control, with all scenarios producing successful outcomes. The application significantly improves the CSIRT team's effectiveness and efficiency in responding to cyber threats. The results confirm the system’s readiness for operational deployment and its potential contribution to enhancing cyber threat intelligence for Institution X and other government agencies.